Foreign language reading strategy use of intermediate level adult Turkish EFL learners - Fatma Aydin; Ozgur Yildirim (Journal on English as a Foreign Language, 2017)
The purpose of this study was to investigate foreign language reading strategy use of a group of intermediate level adult Turkish EFL learners. The participants of the study were 87 Turkish first-year university students who were taking intermediate level English courses at a state university in Turkey. The main instrument of the study was a reading strategies survey which consisted of 30 items with three sub-scales: global or metacognitive reading strategies, problem-solving or cognitive reading strategies, and support reading strategies. Semi-structured interviews were also conducted to support the quantitative data. The quantitative data were analyzed using descriptive statistics (mean, standard deviation, frequencies, percentages) and one-way ANOVA with repeated measures. As for the analysis of the qualitative data, tape-recorded interviews were first transcribed and then analyzed by grouping each interviewee